Confucianism and learners’ performance in argumentative writings in English: Insights from a Vietnamese context : - Trịnh, Khắc Thái (Đại học Cần Thơ, 2011)
The research aims to find out Confucian ethical thoughts and teaching manifesting in Vietnamese learners’ English argumentative writing and its impact on their argumentative essays